SLEEP AND STROKE: features of occurrence and course - Yakubova, M.M.; Shermuhamedova, F.Q.; Abzalova, M.B.; Nishonova, Yu.U.; Shokirov, Sh.Sh. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Cerebrovascular diseases, such as ischemic and hemorrhagic strokes, are among the leading causes of disability and mortality worldwide. Evidence shows us that the identification and treatment of sleep disorders should be included in both primary and secondary stroke prevention. Sleep and stroke are often intertwined because sleep disorders, including sleep-disordered breathing, parasomnias, sleep-related movement disorders, insomnia, and hypersomnia, are closely associated with comorbid cardiovascular disease and increase the risk of stroke. Sleep disturbances after stroke can also affect stroke rehabilitation and quality of life, and if left untreated can lead to recurrent strokes.